Effects of calcination conditions on phase formation and particle size of Zn2Nb34O87 powders synthesized by solid-state reaction - Penphitcha Amonpattaratkit (2018)
Phase formation and particle size of Zn 2 Nb 34 O 87 powders which were synthesized by a solid state reaction via a simple vibro-milling technique have been investigated as a function of calcination conditions, for the first time, by using a combination of X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX) techniques. In general, the results shown that increasing calcination temperature, dwell time or heating/cooling rates can effectively increase both purity and particle size of the desired Zn 2 Nb 34 O 87 powders. Moreover, It has been found that the optimization of calcination condition (900°C, 1 h, 20°C/min) can successfully lead to a single-phase of submicrometer-sized Zn 2 Nb 34 O 87 powders.